Numerical study on heat transfer enhancement of PCM using three combined methods based on heat pipe. (15th March 2020) - Zhang, Chunwei; Yu, Meng; Fan, Yubin; Zhang, Xuejun; Zhao, Yang; Qiu, Limin
Abstract: The latent thermal energy storage (LTES) system, which uses phase change materials (PCMs), has received a great deal of attention as an effective means of storing thermal energy. However, because of the low thermal conductivity of most PCMs, there is still an urgent need to develop efficient heat transfer enhancement techniques. In this study, a novel combination of heat pipe-fins-copper foam (HP-Fin-CF) has been proposed, and its performance was evaluated via comparisons to the performances of HP-Fin and HP-CF combinations. The effective heat capacity method and thermal resistance network are used in numerical modeling. The results indicate that the HP-Fin combination has better melting performance, whereas the HP-CF combination leads to better solidification. Compared with the basic HP configuration, the total time for melting and solidification can be reduced by 82.70%, 89.03%, and 93.34% for the HP-Fin, HP-CF, and HP-Fin-CF combinations, respectively. The evolution of melting rates suggests that natural convection accelerates the melting of the PCM with the HP-Fin and HP-Fin-CF combinations, but may extend the complete melting time of the PCM in the HP-CF combination under some specific conditions. Also, the exergy analysis was performed to study the thermodynamic properties of the three combinations. Highlights: Three combined methods based on HP are proposed for heat transfer enhancement. The evolution of melting rates is used to study the heat transfer mechanism. The HP-Fin improves melting better while the HP-CF leads to better solidification. The complete cycle time of the PCM with the HP-Fin-CF is decreased by 93.34%. The exergy analysis on the complete energy storage cycle is carried out.